Respostas
respondido por:
6
2x + 2y = 126
x + y = 63
x * y = 972
Fazendo um sistema com as duas:
y = 63 - x
x*(63-x) = 972
63x - x^2 = 972
-x^2 + 63x - 972 = 0
Delta = 3969 - 4 * (-1) * 972
Delta = 3969 + 3888
Delta = 7857
raiz(delta) = 9*raiz(97)
x1 = (-63 + 9*raiz(97))/(-2) = (63 + 9*raiz(97))/2
x2 = (-63 - 9*raiz(97))/(-2) = (63 - 9*raiz(97))/2
Acho eu que esta errado :P resposta feia
x + y = 63
x * y = 972
Fazendo um sistema com as duas:
y = 63 - x
x*(63-x) = 972
63x - x^2 = 972
-x^2 + 63x - 972 = 0
Delta = 3969 - 4 * (-1) * 972
Delta = 3969 + 3888
Delta = 7857
raiz(delta) = 9*raiz(97)
x1 = (-63 + 9*raiz(97))/(-2) = (63 + 9*raiz(97))/2
x2 = (-63 - 9*raiz(97))/(-2) = (63 - 9*raiz(97))/2
Acho eu que esta errado :P resposta feia
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás